Asymmetric Electrolytes Design for Aqueous Multivalent Metal Ion Batteries - Xiaochen Yang; Xinyu Wang; Yue Xiang; Longtao Ma; Wei Huang (Nano-Micro Letters, 2023)
Highlights The working principle of the asymmetric electrolyte and the long-term-seated contradictory issues were analyzed. The characterization methods for the interfaces of anolyte/catholyte and electrolyte/electrode were summarized for revealing the fundamental mechanism of asymmetric electrolytes. The future research directions for asymmetric electrolyte systems were proposed.